2021
DOI: 10.1109/jstars.2021.3090792
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Highly Accurate Shallow Water Bathymetry From Sentinel-2 and ICESat-2 Datasets by a Multitemporal Stacking Method

Abstract: Empirical models have been widely used to retrieve shallow water bathymetry from multispectral/hyperspectral satellite imagery. In traditional studies on deriving the topography and monitoring its temporal changes, a single date satellite image without clouds corresponded to a bathymetric map and multi-date images corresponded to multiple bathymetric maps. The satellite image noise caused by various environmental conditions and satellite sensors can inevitably introduce errors or gaps in deriving bathymetric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Moreover, it can be concluded that integration of harmonised L8/OLI and S2A/MSI imagers may minimize the errors which are usually come from atmospheric interferences, and consequently may increase the final estimated depth values. However, many studies showed that, in comparison with single image, the use of multitemporal Sentinel-2 images may improve the estimated bathymetric data (Evagorou et al, 2019;Xu et al, 2021;Lumban-Gaol et al, 2022). It should be noted that Landsat-9 satellite has launched on September 2021with the same OLI imager and an 8-day time interval with Landsa-8 satellite.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can be concluded that integration of harmonised L8/OLI and S2A/MSI imagers may minimize the errors which are usually come from atmospheric interferences, and consequently may increase the final estimated depth values. However, many studies showed that, in comparison with single image, the use of multitemporal Sentinel-2 images may improve the estimated bathymetric data (Evagorou et al, 2019;Xu et al, 2021;Lumban-Gaol et al, 2022). It should be noted that Landsat-9 satellite has launched on September 2021with the same OLI imager and an 8-day time interval with Landsa-8 satellite.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the above mentioned models for SDB are supervised learning based models, where the models are trained to estimate depth of water columns from satellite data/images using certain ground truth data. The works use depth information collected from acoustic systems [11]- [13], [15], [16], [20]- [23], [31]- [35], airborne LiDAR systems [10], [11], [14], [17], [19], [26], [28], [36]- [38] or LiDAR data obtained from Ice, Cloud, and Elevation Satellite-2 (ICESat-2) satellites [18], [29], [30], as ground truth data. The study areas of interest in most of the above works belong to coastal regions [10]- [12], [14], [15], [17]- [19], [21], [28], [32], [34], [37], [39] and only a small number of works study SDB for inland water bodies [13], [16], [38].…”
Section: A Literature Surveymentioning
confidence: 99%
“…The works use depth information collected from acoustic systems [11]- [13], [15], [16], [20]- [23], [31]- [35], airborne LiDAR systems [10], [11], [14], [17], [19], [26], [28], [36]- [38] or LiDAR data obtained from Ice, Cloud, and Elevation Satellite-2 (ICESat-2) satellites [18], [29], [30], as ground truth data. The study areas of interest in most of the above works belong to coastal regions [10]- [12], [14], [15], [17]- [19], [21], [28], [32], [34], [37], [39] and only a small number of works study SDB for inland water bodies [13], [16], [38]. As mentioned, most of the above works consider the reflectance values collected by satellites as input for estimating depth of water columns.…”
Section: A Literature Surveymentioning
confidence: 99%
“…1 It provides the foundation for analyzing shoreline changes and deepens our understanding of the impact of climate change phenomena such as global warming, sea-level rise, ocean acidification, and pollution on nearshore environments. 2,3 High-precision bathymetric data offer invaluable information for coastal geomorphological analysis, navigational safety, sediment studies, fisheries, mineral exploration, coastal engineering, and resource conservation. [4][5][6] While traditional shipborne multibeam echo sounders perform well in deeper waters, they pose higher risks in shallow waters with corals and rocks.…”
Section: Introductionmentioning
confidence: 99%